2020
DOI: 10.3390/vaccines8020262
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the Gene for the Type I Interferon Inhibitor I329L from the Attenuated African Swine Fever Virus OURT88/3 Strain Reduces Protection Induced in Pigs

Abstract: Live attenuated vaccines are considered to be the fastest route to the development of a safe and efficacious African swine fever (ASF) vaccine. Infection with the naturally attenuated OURT88/3 strain induces protection against challenge with virulent isolates from the same or closely related genotypes. However, adverse clinical signs following immunisation have been observed. Here, we attempted to increase the OURT88/3 safety profile by deleting I329L, a gene previously shown to inhibit the host innate immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 26 publications
1
39
0
Order By: Relevance
“…In the latest study in May 2020, an attempt was made to increase the safety of the naturally attenuated strain OURT88/3 by deleting I329L, a gene previously shown to inhibit the innate immune response of the host. Unexpectedly, the OURT88/3∆I329L strain significantly reduced protection against virulent stains OURT 88/1 attacks [ 50 ]. To date, the hinge to immune protection of naturally LAVs still needs to be further elucidated.…”
Section: Current State Of Asf Vaccine Developmentmentioning
confidence: 99%
“…In the latest study in May 2020, an attempt was made to increase the safety of the naturally attenuated strain OURT88/3 by deleting I329L, a gene previously shown to inhibit the innate immune response of the host. Unexpectedly, the OURT88/3∆I329L strain significantly reduced protection against virulent stains OURT 88/1 attacks [ 50 ]. To date, the hinge to immune protection of naturally LAVs still needs to be further elucidated.…”
Section: Current State Of Asf Vaccine Developmentmentioning
confidence: 99%
“…For example, infection with a naturally attenuated OURT88/3 strain induced protection against the same or closely related strains but simultaneously caused side effects. Reis et al [ 60 ] attempted to increase the vaccine’s safety by deleting the I329L gene. Surprisingly, the protection induced by the OURT88/3ΔI329L deletion mutant was significantly reduced against challenge with the virulent OURT88/1 isolate.…”
Section: Vaccines Against Asf—a Short Review and The Latest Achievementsmentioning
confidence: 99%
“…A decrease in the level of antibodies against ASFV protein VP72/B646L and the number of IFN-γ-producing cells in the blood was observed in unprotected animals, while the concentration of IL-10 in the serum of animals immunized with OURT88/3ΔI329L was increased. The same study also showed that the deletion of the I329L gene fails to attenuate the virulent Georgia/2007 isolate [ 60 ]. Previous studies showed that the deletion of another IFN inhibitor (A276R) from the NH/P68 isolate resulted in a complete loss of protection against Arm07 challenge, as opposed to the complete protection provided by vaccination with wild-type NH/P68 [ 67 ].…”
Section: Vaccines Against Asf—a Short Review and The Latest Achievementsmentioning
confidence: 99%
See 2 more Smart Citations